The human factor in industry - Keane, John (Statistical and Social Inquiry Society of Ireland, 1941)
I do ask you to interpret industry in its widest sense as covering not merely factories and organised business but human relations in all professions and individual occupations. Almost all the real difficulties of life arise from temperament, prejudice, stupidity, lack of understanding and the vast interaction of these elusive indeterminate factors. It is on account of this very elusiveness and lack of any fixed standard by which to measure human behaviour that many doubt whether the human factor is capable of any systematic or quasi-scientific treatment in the day to day dealings of life. These people say: Human nature is ever the same and unchangeable; free will cannot be brought within the ambit of any general code of conduct!
Read on Thursday, 23rd January, 1941
Keywords: Human needs; Worker performance; 314.15